High arsenic contamination in the breast milk of mothers inhabiting the Gangetic plains of Bihar: a major health risk to infants - Arun Kumar; Radhika Agarwal; Kanhaiya Kumar; Nirmal Kumar Chayal; Mohammad Ali; Abhinav Srivastava; Mukesh Kumar; Pintoo Kumar Niraj; Siddhant Aryal; Dhruv Kumar; Akhouri Bishwapriya; Shreya Singh; et al. (BMC, 2024)
Abstract Groundwater arsenic poisoning has posed serious health hazards in the exposed population. The objective of the study is to evaluate the arsenic ingestion from breastmilk among pediatric population in Bihar. In the present study, the total women selected were n = 513. Out of which n = 378 women after consent provided their breastmilk for the study, n = 58 subjects were non-lactating but had some type of disease in them and n = 77 subjects denied for the breastmilk sample. Hence, they were selected for the women health study. In addition, urine samples from n = 184 infants' urine were collected for human arsenic exposure study. The study reveals that the arsenic content in the exposed women (in 55%) was significantly high in the breast milk against the WHO permissible limit 0.64 µg/L followed by their urine and blood samples as biological marker. Moreover, the child's urine also had arsenic content greater than the permissible limit (< 50 µg/L) in 67% of the studied children from the arsenic exposed regions. Concerningly, the rate at which arsenic is eliminated from an infant's body via urine in real time was only 50%. This arsenic exposure to young infants has caused potential risks and future health implications. Moreover, the arsenic content was also very high in the analyzed staple food samples such as rice, wheat and potato which is the major cause for arsenic contamination in breastmilk. The study advocates for prompt action to address the issue and implement stringent legislative measures in order to mitigate and eradicate this pressing problem that has implications for future generations.